Policies and Practices of Integration: High-Skilled Migrants from India in Singapore. (2nd October 2017) - Chacko, Elizabeth
ABSTRACT: The Singaporean government has employed immigration primarily from China and India to boost the country's working age population and contribute to its economic growth. In this paper I examine the integration of high-skilled migrants from India at the national level and in local urban spaces. I study the role of the state, natives and the immigrants in the integration process, as well as the effectiveness of Singapore's integration policies. Challenges to immigrant integration include hostile reactions from natives, differences in cultural mores between immigrants and natives, and a lack of transparency on the effects of government policies on local populations.